2005
DOI: 10.1108/14754390580000833
|View full text |Cite
|
Sign up to set email alerts
|

How O2 built the business case for engagement

Abstract: Like any successful HR initiative, employee engagement programs must have commitment from line managers. Find out how O2 revisited its employee engagement efforts and why demonstrating a robust business case is essential to getting and maintaining buy‐in from leaders and managers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…anecdotal (along with some empirical) evidence that employee engagement results in improved employee performance (Smythe, 2008;Walters, 2008;Chang, 2006;Crawford, 2006;Echols, 2005;Tasker, 2004;Luthans and Peterson, 2002;Tritch, 2003a, b); or . ways, means, or methods by which organizations or individual managers can improve or enhance an employee's level of engagement (Fenci and Masarech, 2008;Cartwright and Holmes, 2006;Konrad, 2006;Seijts and Crim, 2006;Harley et al, 2005;Sensis, 2005;Erickson, 2004;Tritch, 2003a, b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…anecdotal (along with some empirical) evidence that employee engagement results in improved employee performance (Smythe, 2008;Walters, 2008;Chang, 2006;Crawford, 2006;Echols, 2005;Tasker, 2004;Luthans and Peterson, 2002;Tritch, 2003a, b); or . ways, means, or methods by which organizations or individual managers can improve or enhance an employee's level of engagement (Fenci and Masarech, 2008;Cartwright and Holmes, 2006;Konrad, 2006;Seijts and Crim, 2006;Harley et al, 2005;Sensis, 2005;Erickson, 2004;Tritch, 2003a, b).…”
Section: Introductionmentioning
confidence: 99%
“…An ABI Inform search using the term “employee engagement” results in a list of 927 papers since 2000. Most of these papers offer either:anecdotal (along with some empirical) evidence that employee engagement results in improved employee performance (Smythe, 2008; Walters, 2008; Chang, 2006; Crawford, 2006; Echols, 2005; Tasker, 2004; Luthans and Peterson, 2002; Tritch, 2003a, b); orways, means, or methods by which organizations or individual managers can improve or enhance an employee's level of engagement (Fenci and Masarech, 2008; Cartwright and Holmes, 2006; Konrad, 2006; Seijts and Crim, 2006; Harley et al , 2005; Sensis, 2005; Erickson, 2004; Tritch, 2003a, b). Optimism, while not discussed nearly as much in the literature, has also been linked to higher levels of employee performance (Jensen et al , 2007; Dixon and Schertzer, 2005; Green et al , 2004; Chemers et al , 2000; Schulman, 1999; Sujan, 1999a, b; Rich, 1999; Scheier et al , 1994; Strutton and Lumpkin, 1993; Seligman and Schulman, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Initial categories that proved helpful in putting "flesh on the bones" of the construct (Miles & Huberman, 1994, p. 27) included working definition, outcomes of engagement, key engagement process theories, and factors associated with the development of engagement. We also identified purely emergent themes, for example, how fear of failure and interpersonal competition can suppress engagement (Newman, 1989), and the notion that different people require different engagement drivers (D'Aprix & Tyler, 2006;Harley & Lee, 2005). Inductive coding was used to surface underlying categories, themes and patterns, and these became the "cornerstones" of the elaborated model proposed here (Strauss & Corbin, 1998, p. 7).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, EE has become a key issue for organisations in the last century (Leadership Insights, 2011). Engaged employees could be claimed to be more motivated, be better at improving themselves, and be productive (Clampitt and Downs, 1993;Harley et al (2005). They could also understand and align themselves with the culture of their companies and the business strategies of organisations as suggested by Coleman (2005).…”
Section: Employee Engagement (Ee)mentioning
confidence: 99%
“…Engaged employees are the ones who are intellectually and emotionally committed to their jobs, and thus they want to give their best effort to their jobs (Sias, 2005). The employees who exhibit such effort are claimed to have positive attitudes towards their jobs; better belief in and better identification with their organizations, and they also work hard to make things at the organisation better; treat others respectfully and encourage their colleagues for better performance; meet the requirements of their jobs; remain up to date about their field; and look for opportunities to improve their organizational performances (Harley et al, 2005). Besides, Baumruk et al (2006) suggested the following behaviours for the engaged employees: they defend their organizations; they are motivated to be a key element of their organizations despite some other external opportunities; they spare extra effort, and they start a new initiative to help their organizations to grow.…”
Section: Employee Engagement (Ee)mentioning
confidence: 99%